TANGGUNG JAWAB HOTEL TERHADAP KEHILANGAN BARANG TAMU SELAMA MENGINAP (STUDI KASUS HOTEL GRIYA WISATA MULYA DI KLATEN) - Rafi’ Purnomo Cahyo Utomo; M. Junaidi (CV. Lafadz Jaya, 2026)
The hospitality industry is a service sector that plays a vital role in supporting the development of tourism and business activities. In the provision of hotel services, the legal relationship between the hotel and the guest extends beyond a mere provider-user dynamic; it also imposes an obligation on the hotel to ensure the security, comfort, and safety of guests and their belongings during their stay. However, in practice, incidents of lost guest property still frequently occur, leading to disputes regarding liability for such losses. The issue is further complicated by the fact that not all losses stem from hotel negligence; they may also result from the guest's own negligence or the use of standard contract clauses that limit or shift the hotel's liability. These circumstances necessitate a deeper examination of the nature of a hotel's legal liability for lost guest property under applicable Indonesian law. This study aims to analyze the hotel's legal liability for lost guest property based on Articles 1709 through 1713 of the Indonesian Civil Code which govern the liability of lodging operators regarding guest property and Law Number 8 of 1999 concerning Consumer Protection. Additionally, the study seeks to examine how this liability is implemented in resolving cases of lost property at Hotel Griya Wisata Mulya Klaten, as well as to identify the obstacles the hotel faces in providing legal protection to consumers and to propose solutions for enhancing the effectiveness of such protection. This research employs an empirical-juridical method with a normative approach. The juridical approach involves analyzing relevant statutory regulations concerning hotel liability and consumer protection, while the empirical approach entails directly observing the application of these legal provisions at Hotel Griya Wisata Mulya Klaten. Primary data were obtained through in-depth interviews with management, receptionists, and hotel staff, alongside observations of security systems and procedures for handling lost property incidents. Meanwhile, secondary data were obtained through a literature review comprising laws and regulations, legal texts, scholarly journals, internal hotel documents, Standard Operating Procedures (SOP), lost-property report forms, and other supporting documents. All data were analyzed qualitatively to gain insight into the alignment between legal provisions and actual practices in the field. The research findings indicate that Hotel Griya Wisata Mulya has implemented legal protection measures for guests through both preventive and repressive means. Preventive protection is realized by providing security facilities such as CCTV and in-room safes conducting security patrols, and implementing Standard Operating Procedures (SOPs) to maintain the security of the hotel premises. Meanwhile, repressive protection is carried out through mechanisms such as accepting loss reports, documenting loss incidents via official reports, reviewing CCTV footage, conducting internal investigations, and resolving disputes through deliberation and the provision of compensation if the loss is proven to stem from hotel negligence. An analysis of a case involving the loss of a guest's mobile phone on the hotel terrace revealed that the hotel bore no legal liability, as the loss resulted from the guest's own negligence in leaving valuables in a public area rather than utilizing the storage facilities provided by the hotel. The research also identified various obstacles in the implementation of legal protection, including limited surveillance systems in certain hotel areas, low guest awareness regarding the safeguarding of personal belongings, inconsistent employee understanding of the hotel's legal liabilities, and the continued use of standard contract clauses that potentially conflict with the provisions of the Consumer Protection Law. Based on these findings, it can be concluded that the hotel's liability for the loss of guest property is not absolute; rather, it depends on establishing the cause of the loss, in accordance with the Civil Code and the Consumer Protection Law. The hotel is obligated to provide protection and compensation if a loss occurs due to its negligence, yet it may be absolved of liability if the loss results from the guest's own fault or negligence, or from force majeure. Therefore, enhancing security systems, eliminating standard clauses that disadvantage consumers, improving human resource competence, and refining dispute resolution mechanisms are necessary steps to ensure optimal legal protection for hotel service consumers and to provide legal certainty for both parties.